Pengembangan media pembelajaran dart board math bagi siswa kelas VII SMP - Desi Listiani; Erlina Prihatnani (STKIP PGRI Banjarmasin, 2018)
The low ability of students in algebra is challenging for teachers to make innovation in the learning of algebra. This research aims to create learning media to help students in learning algebra. The model used for the development of this research is ADDIE, which consists 5 stages, such as Analyze, Design, Development Implementation, and Evaluation. This research produces a product of interactivelearning media called Dart Board Math. The instruments used consist of media validation sheet, praticality sheete, pre test, post test, and students’ argument sheet. This media has been applied to 26 students in the 2nd Grade of Junior High School 2 Salatiga. The Dart Board Math has been classified as as valid from both material aspect and learning media aspect with precentage of 88,1% and 89,1% which are both classified as excellent. The precentage os praticality test result is 84,1% which is classified as excellent. Pair t-test of significance level of 5% produce significance approaching zero with post test average higher than the pre test. Based on the three test that has been implemented, this meda of learing is classified to be valid, pratical and effective